2021
DOI: 10.1002/cam4.4339
|View full text |Cite
|
Sign up to set email alerts
|

Potential utility of longitudinal somatic mutation and methylation profiling for predicting molecular residual disease in postoperative non‐small cell lung cancer patients

Abstract: Growing efforts are being invested in investigating various molecular approaches to detect minimal residual disease (MRD) and predict disease recurrence. In our study, we investigated the utility of parallel longitudinal analysis of mutation and DNA methylation profiles for predicting MRD in postoperative non‐small‐cell lung cancer (NSCLC) patients. Tumor tissues and longitudinal blood samples were obtained from 65 patients with resected stage IA‐IIIB NSCLC. Somatic mutation and DNA methylation profiling were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have reported low frequency [ 11 , 12 ] and dynamic changes [ 13 , 14 ] in somatic variants. Therefore, to our knowledge, we performed multiple ddPCR detections on 11 patients with RP using blood samples collected at different follow-up time points for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported low frequency [ 11 , 12 ] and dynamic changes [ 13 , 14 ] in somatic variants. Therefore, to our knowledge, we performed multiple ddPCR detections on 11 patients with RP using blood samples collected at different follow-up time points for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…84 Longitudinal methylation profiling along with somatic mutation analysis in patients with NSCLC have also shown prognostic potential in assessing the risk of recurrence. 85 With regard to its prognostic value, the level of ctDNA was found indicative of lymph node involvement in resectable NSCLC. 86 Other investigators collected tissue and plasma samples from NSCLC patients before and after surgery in order to identify driver mutations in genes, including EGFR, KRAS, TP53, BRAF, PIK3CA, and ERBB2.…”
Section: Circulating Tumor Dnamentioning
confidence: 99%
“…Previous studies have demonstrated the power of longitudinal molecular pro ling in tracking tumour evolution and identifying therapeutic targets in cancer patients [1,2]. More recent investigation on population cohorts showcased how longitudinal molecular pro ling aided in predicting treatment outcomes and tailoring interventions for patients with chronic diseases [3,4]. However, when health outcomes are recorded, there may be a lack of biosamples available to measure the molecular changes occurring at that time.…”
Section: Introductionmentioning
confidence: 99%